Foreign banks, financial crises and macroeconomic fluctuations1. Issue 3 (8th June 2016) - Önder, Zeynep; Özyıldırım, Süheyla
Abstract: Understanding the implications of increased foreign bank presence is especially compelling in periods of financial crisis. In this paper, we explore this issue by examining the relationship between the involvement of foreign banks in the banking systems and the volatility of key macroeconomic variables in normal and crisis periods. Using a sample of 20 Emerging European countries from 1998 to 2013, we find that an increase in the assets of foreign banks in the banking system reduces output and consumption growth volatility in general but does not significantly affect the volatility of investments. However, these banks were found to play a significant role in increasing output, consumption and investment volatility in 2009. Our findings suggest that foreign banks' harmful impact during the global crisis was only temporary and that they seem to help Emerging European countries stabilize macroeconomic volatility in normal times and after the global crisis.